Septicemia due to Capnocytophaga canimorsus following dog bite in an elderly male - Sowmya Chary; Megha Joshi; Sriharshan Reddy; Cheryl Ryan; Venu Saddi (Wolters Kluwer Medknow Publications, 2011)
A previously healthy, 67-year-old, man with past medical history of myocardial infarction and hypertension was rushed to the emergency room after sudden onset of fever, chills, severe rigors, hypotension, tachycardia and vomiting. The patient was diagnosed as being in septic shock, and investigations revealed intracellular gram-negative bacilli in polymorphonuclear leukocytes in the peripheral smear. A history of dog contact was elicited after this very unusual and rare finding. Cultures confirmed septicemia due to Capnocytophaga canimorsus, a normal oral and nasal flora inhabitant of cats and dogs that can cause severe and sometimes fatal septicemia in humans. We report this very interesting case because of the common prevalence of dog homeownership and the rarity of C. canimorsus inducing sepsis.